Influência dos fatores organizacionais no sucesso de projetos no setor automotivo - Santos, Izabela Andressa Machado dos [UNESP] (2015)
This research aims to identify and to evaluate the organizational factors influencing project success in automotive companies to contribute to project management area. Project success relates to the ability to achieve the objectives proposed. Organizational factors are critical to an organization and they are considered crucial to organizational success as well as company's project success. The effectiveness of a company depends in part on its project sucess. And an important factor regarding to project is to determine the success factores because they allow evaluation and correction during the execution phase as well as learning for future projects. The questionnaire developed for this survey was sent to 401 Brazilian automotive companies which are members of SINDPEÇAD and also to the participants of the Gerenciamento de Projetos Automotivos (Automotive Project Management) group on Linkedin. We obtained 72 responses which were used in this study. Quantitative methods were used to ansewer the research questions. First, we used confirmatory factor analysis to identify the organizational factors that influence project success. The results of this analysis indicated that top management support, good communication, effective change management, organizational culture and training have a positive influence to the project success. Then we applied a multiple linear regression and we found a model that best fits the data. According to the results of this analysis, the organizational factor that has the highest rate influences to the success is the organizational culture, followed by top management support and by effective change management. From an organizational point of view, this study allows managers to analyze and understand the organizational factors present and their influences on project success, enabling better priorization and monitoring of projects, not limited only to technical issues. Based on the results, we noticed that most of...